Case Report: Clinicopathological and Genetic Features of IDH-Mutant Brainstem Glioma in Adults: Report of Five Cases - Jiangfen Zhou; Mingyao Lai; Yang Ni; Shaoqun Li; Junjie Zhen; Furong Du; Xing Zhang; Chao Song; Linbo Cai (Frontiers Media S.A., 2022)
Adult brainstem gliomas are rare central nervous system tumors that represent a heterogeneous group of tumors. Somatic IDH mutations are uncommon in adult brainstem gliomas and there are few relevant clinical studies. Here, we reported five patients with IDH1 mutations associated with brainstem gliomas, including four cases of IDH1 R132H mutations and one case of R132G mutation. All patients were treated with focal intensity-modulated radiation therapy (IMRT) with concurrent temozolomide (TMZ). One patient died, one relapsed, and three survived to date. All these cases carried a pathogenic variant of TP53, among whom 1 harbored ATRX mutation and 1 had H3K27M mutation. Moreover, we also found some genes related to a worse prognosis, such as CDK4/6 amplification. These findings demonstrate that the specific characteristics of IDH-mutant brainstem gliomas should be considered in diagnostic workflows to make therapeutic regimens and improve the prognosis.